High-temperature molecular beam epitaxy of hexagonal boron nitride layers - Cheng, Tin S.; Summerfield, Alex; Mellor, Christopher J.; Davies, Andrew; Khlobystov, Andrei N.; Eaves, Laurence; Foxon, C.T.; Beton, Peter H.; Novikov, Sergei V. (AIP Publishing, 2018)
The growth and properties of hexagonal boron nitride (hBN) have recently attracted much attention due to applications in graphene-based monolayer thick 2D-structures and at the same time as a wide band gap material for deep-ultraviolet device (DUV) applications. We present our results on the high-temperature plasma-assisted molecular beam epitaxy (PA-MBE) of hBN monolayers on highly oriented pyrolytic graphite (HOPG) substrates. Our results demonstrate that PA-MBE growth at temperatures ~1390 oC can achieve mono- and few-layer thick hBN with a control of the hBN coverage and atomically flat hBN surfaces which is essential for 2D applications of hBN layers. The hBN monolayer coverage can be reproducible controlled by the PA-MBE growth temperature, time and B:N flux ratios. Significantly thicker hBN layers have been achieved at higher B:N flux ratios. We observed a gradual increase of the hBN thickness from 40 to 70 nm by decreasing the growth temperature from 1390 oC to 1080 oC. However, by decreasing the MBE growth temperature below 1250 oC, we observe a rapid degradation of the optical properties of hBN layers. Therefore, high-temperature PA-MBE, above 1250 oC, is a viable approach for the growth of high-quality hBN layers for 2D and DUV applications.